Sustainability vs. profitability: does socially responsible investing correlate to increased profits? - Michel, Malia, author (Colorado State University. Libraries, 2016)
I am analyzing the link between companies who utilize sustainability practices in their business and the positive influence that can have on earnings. Specifically, looking at Bloomberg's Environmental, Social, and Governance (ESG) scores and the companies earning announcements. I am trying to prove the significance of doing good for the planet will positively correlate to an increase in profits.
Keywords: industries; historical prices; earnings per share